A novel peptide-based electrochemical biosensor for breast cancer characterization over a poly 3-(3-aminophenyl) propionic acid matrix - da Fonseca Alves, Rafael [UNESP]; Martins, Isabella Castro; Franco, Diego Leoni; Silva, Adriane das Graças; de Souza Santos, Paula; Goulart, Luiz Ricardo; Cristina de Paiva Maia, Yara; Faria Silva, Alinne Tatiane; Gonçalves Araújo, Thaise; Del Pilar Taboada Sotomayor, Maria [UNESP] (Elsevier, 2022)
In this work, a new electrochemical biosensor was developed using peptides selected by Phage Display as biorecognition phase to Breast Cancer (BC) characterization. Phage clones were selected against MCF-7 (ER-positive BC) proteins, in order to characterize patients with aggressive luminal BC. Biotin-C3 and biotin-H2 peptides were chemically synthesized and validated by flow cytometry, immunofluorescence assays, and ELISA assays, being more reactive to the MCF-7 lineage. Furthermore, a new matrix for the coupling of biomolecules on the surface of graphite electrodes was generated, through electrochemical modification with a new material derived from 3-(3-aminophenyl)propionic acid (3-3-APPA). Electrochemical and morphological characterizations were carried out, and the mechanism of electropolymerization of poly(3-3-APPA) was proposed, in which the carboxylate groups are kept in the structure of the formed polymer. Then, a biosensor was developed by immobilizing the biotin-C3 and biotin-H2 peptides in the SPE/poly(3-3-APPA)/avidin system for the detection of BC tumor markers in serological samples. Finally, peptides were validated using samples from patients with BC and Benign Breast Disease. Biotin-C3 peptide characterized luminal BC according to p53 status and to HER2 expression, being the biosensor a better strategy when compared to ELISA test. This new biosensor will open a new perspective for a rapid and electrochemical platform for the characterization of BC and its molecular subtypes.
Keywords: 3-(3-Aminophenyl)propionic acid; Biosensors; Breast cancer; Modified electrodes; Phage display